Same Language, Different Diet. (20th January 2022) - Sinner, Alejandro G.; Nieto-Espinet, Ariadna; Valenzuela-Lamas, Silvia
Abstract : This study uses faunal and epigraphic evidence from the valley of Cabrera de Mar in present-day Catalonia (Spain) as proxies for understanding complex processes and dynamics of cultural change between the late Iron Age and early Roman times. The faunal remains indicate significant dietary change, although the epigraphic evidence implies that language—in contrast—changed at a slower pace, as shown by the use of indigenous onomastics and the continued use of the Iberian script, coin legends included. To ensure an interdisciplinary analysis, the study also discusses change as perceptible in architectural remains, ceramics and funerary practices. Our study shows that cultural change can take place at different levels and according to different rhythms, not only on regional and settlement planes but also at neighbourhood and household scales. Finally, our results highlight the value of archaeology as a tool for studying and understanding colonial encounters.